Integrated Library Automation Experience of NAL Using PCs - Murthy, S. G. K.; Prasanna Kumari, K. N.; Garudadwajan, B. (Journal of Information and Knowledge, 2014)
In this paper the library atuomation system established using dBase3 in ICA/NAL, is presented, including the Library Documentation Acquisition system. From the system we can generate various service by-products, such as reminders for over - due documents to the vendors, financial status, order generation, accession lists, recent book additions, etc. The aim is to input relevant data at appropriate stages of the automation system and integrate it with the library acquisition, circulation, and generation of current acquisition lists, and develop an appropriate Information retrieval system. The sailent features of the system are discussed.